Substitutions of soybean meal with enriched palm kernel meal in laying hens diet - Sinurat, Arnold P.; Purwadaria, Tresnawati; Ketaren, Pius P.; Pasaribu, Tiurma (Indonesian Journal of Animal and Veterinary Sciences, 2014)
A series of experiment was conducted in order to substitute soybean meal (SBM) with palm kernel cake (PKC) as a protein source in laying hens diet. First experiment was to increase its protein and amino acids content by fermentation process and followed by enzymes supplementation to improve nutrient digestibilities. Second experiment was conducted to evaluate the effectiveness of enzyme- supplemented fermented palm kernel cake (EFPKC) to replace SBM in laying hens diet. The energy (AME) of the PKC, the fermented PKC (FPKC) and the EFPKC was measured by ileal amino acids digestibility (IAAD) in broilers. The AME and the IAAD values of the EFPKC were used for diet formulation in the feeding trial. A feeding trial was performed in laying hens, aged 51 weeks for 8 weeks egg production. Five diets with different levels of substitution of SBM with EFPKC but similar nutrient contents were formulated, i.e.: 1. Control (without EFPKC), 2. 25% of SBM in control diet substituted with EFPKC, 3. 50% of SBM in control diet substituted with EFPKC, 4. 75% of SBM in control diet substituted with EFPKC and 5. 100% of SBM in control diet substituted with EFPKC. Each diet was fed to 24 hens (6 replicates of 4 birds/ replicate). Results of the experiment showed that the fermentation of PKC increased the crude protein and most of the amino acids contents except the threonine and arginine, but decreased its AME.Â  Supplementation of enzymes (BS4 or CE) improved the ileal amino acid digestibilities of the fermented PKC. However, only BS4 enzymes increased the AME of the EFPKC. About 25% to 50% of the SBM in the diet could be substituted with the EFPKC without any detrimental effect on the performances of laying hens. Key Words: Soybean Meal, Palm Kernel Cake, Fermentation, Enzyme, Egg Production